Capturing the dynamic association between a tris-dipicolinate lanthanide complex and a decapeptide: a combined paramagnetic NMR and molecular dynamics exploration. Issue 19 (19th March 2021) - Denis-Quanquin, Sandrine; Bartocci, Alessio; Szczepaniak, Florence; Riobé, Francois; Maury, Olivier; Dumont, Elise; Giraud, Nicolas
Abstract : We combine NMR and molecular dynamics to decipher the dynamic supramolecular association process between a peptide and a lanthanide complex. Abstract : In the realm of biomolecules, peptides can present a large diversity of structures. Our study sheds new light on the structural interplay between a tris-dipicolinate lanthanide probe and a decapeptide SASYKTLPRG. Although a rather trivial, electrostatically driven interaction was expected, the combination of paramagnetic NMR and molecular dynamics simulations reveals a highly dynamic association process and allows for providing extensive insights into the interaction sites and their occupancy. This study highlights the importance of a large conformational sampling to reconcile characteristic time in NMR with molecular dynamics simulations, where sampling in the microsecond range is needed. This study opens the door for a detailed mechanistic elucidation of the early steps of lanthanide complex-peptide or lanthanide complex–protein interaction or self-assembly processes.